Hearing parameters in noise exposed industrial workers - Çelik, Onur; Yalçin, Şinasi; Öztürk, Ahmet (My University, 1998)
This paper presents the results of a study carried out in a group of noise-exposed workers in a hydro-electric power plant. Thus, the main focus of the study is on 130 industrial workers who were exposed to high level of noise. The control group was consisted of 33 subjects with normal hearing. Hearing and acoustic reflex thresholds were obtained from all subjects and the results from age-matched subgroups were compared. The sensorineural hearing loss which were detected in 71 workers were bilateral, symmetrical and affected mainly frequencies of 4-6 kHz. In essence, the hearing losses were developed within the first 10 years of noise exposure and associated with slight progress in the following years. When acoustic reflex thresholds derived from the study and control groups were compared, statistically significant difference was determined only for the thresholds obtained at 4 kHz (p < 0.0005).
Keywords: Hearing parameters; Industrial workers; Noise exposure